Museum accession logs for zoology collection, University of Illinois Museum of Natural History - University of Illinois at Urbana-Champaign. Museum of Natural History; Baker, Frank Collins, 1867-1942.; University of Illinois at Urbana-Champaign. Museum of Natural History (Urbana, Illinois, 1918)
This collection consists of accession logs which document the specimens accessioned by the Illinois Museum of Natural History at the University of Illinois. Accessions are primarily mollusks, but include taxa other than mollusks, such as fish and birds. Contributing curators include Frank C. Baker. Recorded information includes catalog number, accession number, taxonomic information, geographic location where specimen was collected, number of specimens accessioned, contributor/donor, collector, date of collection. Note: dates given in this record represent dates of records of accessions to the museum, not the specimen collection dates.
v.1 catalog nos. Z1-Z7524 -- v.2 catalog nos. Z7525-Z14774 -- v.3 catalog nos. Z14775-Z22249 -- v.4 catalog nos. Z22250-Z29800 -- v.5 catalog nos. Z29801-Z37250 -- v.6 catalog nos. Z37251-Z44722
Catalog numbers Z1-Z44722.
Title supplied by cataloger.
Mode of access: Internet.
Keywords: Mollusks -- Catalogs and collections; Zoological specimens -- Catalogs and collections; Museums -- Acquisitions -- Illinois